Signed in Blood: Circulating Tumor DNA in Cancer Diagnosis, Treatment and Screening - Adashek, Jacob J. (Cancers (Basel), 2021)
SIMPLE SUMMARY: An important advance in the diagnostic and surveillance toolbox for oncologists is circulating tumor DNA (ctDNA). This technology can detect microscopic levels of cancer tissue before, during, or after treatment. Various groups from across the globe have published their experiences with the use of ctDNA to either guide therapy or monitor outcomes. The use of ctDNA likely cannot supplant the need for tissue biopsies, but it can complement other diagnostic and therapeutic monitoring mechanisms. ABSTRACT: With the addition of molecular testing to the oncologist’s diagnostic toolbox, patients have benefitted from the successes of gene- and immune-directed therapies. These therapies are often most effective when administered to the subset of malignancies harboring the target identified by molecular testing. An important advance in the application of molecular testing is the liquid biopsy, wherein circulating tumor DNA (ctDNA) is analyzed for point mutations, copy number alterations, and amplifications by polymerase chain reaction (PCR) and/or next-generation sequencing (NGS). The advantages of evaluating ctDNA over tissue DNA include (i) ctDNA requires only a tube of blood, rather than an invasive biopsy, (ii) ctDNA can plausibly reflect DNA shedding from multiple metastatic sites while tissue DNA reflects only the piece of tissue biopsied, and (iii) dynamic changes in ctDNA during therapy can be easily followed with repeat blood draws. Tissue biopsies allow comprehensive assessment of DNA, RNA, and protein expression in the tumor and its microenvironment as well as functional assays; however, tumor tissue acquisition is costly with a risk of complications. Herein, we review the ways in which ctDNA assessment can be leveraged to understand the dynamic changes of molecular landscape in cancers.